2019
DOI: 10.1111/iwj.13094
|View full text |Cite
|
Sign up to set email alerts
|

Variations in study outcomes relative to intention‐to‐treat and per‐protocol data analysis techniques in the evaluation of efficacy for treatment of venous leg ulcers with dehydrated human amnion/chorion membrane allograft

Abstract: Statistical interpretation of data collected in a randomised controlled trial (RCT) is conducted on the intention‐to‐treat (ITT) and/or the per‐protocol (PP) study populations. ITT analysis is a comparison of treatment groups including all patients as originally allocated after randomisation regardless if treatment was initiated or completed. PP analysis is a comparison of treatment groups including only those patients who completed the treatment as originally allocated, although it is often criticised because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The research consistently demonstrates the effectiveness of placental-derived biomaterials to treat diabetic foot ulcers (DFUs) and venous leg ulcers (VLUs). Several of these high-level studies compared the application of placental-derived biomaterials with standard wound care and demonstrated that the application of placental-derived biomaterials significantly improves the proportion of healed ulcers [132,135,137,171,175,181,[184][185][186][187]189,190], time to healing and rates of healing [132,135,137,175,[184][185][186][187]191], and ulcer size [171,180,182,189,191]. In addition, Selena and colleagues [190] reported that 79.5% of patients treated with dHACM and multilayer compression therapy reported reduced VLU pain, compared with 52.4% patients who were treated with multilayer compression therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…The research consistently demonstrates the effectiveness of placental-derived biomaterials to treat diabetic foot ulcers (DFUs) and venous leg ulcers (VLUs). Several of these high-level studies compared the application of placental-derived biomaterials with standard wound care and demonstrated that the application of placental-derived biomaterials significantly improves the proportion of healed ulcers [132,135,137,171,175,181,[184][185][186][187]189,190], time to healing and rates of healing [132,135,137,175,[184][185][186][187]191], and ulcer size [171,180,182,189,191]. In addition, Selena and colleagues [190] reported that 79.5% of patients treated with dHACM and multilayer compression therapy reported reduced VLU pain, compared with 52.4% patients who were treated with multilayer compression therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que avanços recentes na biotecnologia resultaram no desenvolvimento de vários biomateriais para o tratamento de feridas, incluindo bioengenharia de pele cultivada a partir de células de doadores humanos (aloenxertos), como identificada nos estudos de Bianchi et al (2018) e Bianchi et al (2019).…”
Section: Discussionunclassified
“…Hence, the relative cost‐effectiveness of using dHACM outside of secondary care is unknown at this time and it is not possible to predict with any certainty what its cost‐effectiveness might be in primary care. Because the economic analysis was based on the results of a single RCT in non‐healing DFUs, it precludes generalisation of our findings to patients with other wound types, although adjunctive dHACM has been shown to be efficacious in treating non‐healing venous leg ulcers 23 , 24 and difficult‐to‐heal fistulas. 25 Predicting whether the use of dHACM would be cost‐effective in treating these wound types is beyond the remit of this study because the patient pathways and treatment algorithms for non‐healing venous leg ulcers and difficult‐to‐heal fistulas differ from those of non‐healing DFUs.…”
Section: Discussionmentioning
confidence: 99%